Implementation Of Green Accounting To Achieve Sustainable Development - Putri Kadek Goldina Puteri Dewi (UNIVED Press, 2024)
This study examines the implementation of green accounting and environmental issues in Sustainable Development. The population in this study is the hospitality industry in Bali. The research population is 157 hospitality industries in Bali. This study classified the entire population according to strata: beachfront hotels, city center hotels, and mountains. Determination of the sample size is done by calculating the proportional sample, which is determined by calculating 10% of the total population in each stratum and using purposive sampling. The number of samples in this study was 16 hotels. Respondents in this study were accountants and hotel leaders/managers. The data collection method used is a questionnaire analyzed through descriptive statistics. This study uses quantitative analysis with a survey design. The t-test data analysis shows that environmental cost awareness has a significant effect on sustainability development, environmental awareness has no significant effect on sustainability development, and environmental cost knowledge has a significant effect on sustainability development. As well as Based on the survey results and descriptive test data analysis per hotel strata, the highest average is in hotels with highland strata, with an average value of 4.29. This indicates that highland hotels have a robust nature conservation policy due to their involvement in mountainous areas, often areas vulnerable to environmental change.